2013
DOI: 10.1063/1.4816902
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence of pendant droplets on an inclined super-hydrophobic substrate

Abstract: Dynamics of micro droplets, coalescence underneath an inclined hydrophobic surface is explored, experimentally as well as computationally. Such a situation often arises during dropwise condensation, atmospheric dew formation, condensation in green houses, and metal vapor condensation during enrichment process, etc. Coalescence induced instability in the pendant mode is an effective means of passively enhancing heat transfer coefficient during dropwise condensation. Inclined substrates have natural advantages i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…23 experimentally investigated the coalescing dynamics of droplets on highly wettable substrates, and revealed that the width of liquid bridge varying with time follows power law in initial stage. Sellier and Trelluyer 24 also revealed that the liquid bridge varying with time follows power law, and the exponent depends on the driving factors of coalescence. Kapur 22 analyzed the dynamics of contact lines during the coalescence of droplets.…”
Section: Introductionmentioning
confidence: 93%
“…23 experimentally investigated the coalescing dynamics of droplets on highly wettable substrates, and revealed that the width of liquid bridge varying with time follows power law in initial stage. Sellier and Trelluyer 24 also revealed that the liquid bridge varying with time follows power law, and the exponent depends on the driving factors of coalescence. Kapur 22 analyzed the dynamics of contact lines during the coalescence of droplets.…”
Section: Introductionmentioning
confidence: 93%